2022
DOI: 10.1007/s40037-022-00726-8
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for interviewing applicants for medical school admissions: a systematic review

Abstract: Introduction Interviews are commonly used to select applicants for medical school, residency, and fellowship. However, interview techniques vary in acceptability, feasibility, reliability, and validity. This systematic review investigated the effectiveness of different interview methods in selecting the best qualified applicants for admission to medical school and developed a logic model to implement best practices for interviewing. Methods Five electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances. In our study, 77% of the PCCM PDs agreed that VIs allowed them to represent their programs ( 11 ), 64% would prefer VIs because they reduce financial burden ( 15 ), and 59% agreed that the number of applicants increased because of the VI format ( 16 ). This is in alignment with previous survey studies.…”
Section: Discussionmentioning
confidence: 68%
“…Our study found that 61% of PCCM PDs would like to conduct VIs in the future, even under usual circumstances. In our study, 77% of the PCCM PDs agreed that VIs allowed them to represent their programs ( 11 ), 64% would prefer VIs because they reduce financial burden ( 15 ), and 59% agreed that the number of applicants increased because of the VI format ( 16 ). This is in alignment with previous survey studies.…”
Section: Discussionmentioning
confidence: 68%
“…Fourth, researchers should consider training interviewers and using more structured interviewing—particularly the MMI—to improve interviewer reliability. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Using standardized questions may help interviewers cover similar topics with URM applicants as non‐URM applicants, rather than focusing on DEI. Standardized questions have also been proposed as a mechanism to avoid bias in nonstructured interviews 30–33 . Requiring implicit bias training for interviewers can signal a commitment to equity in the recruitment process, although the efficacy of such training is unclear 26,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Standardized questions have also been proposed as a mechanism to avoid bias in nonstructured interviews. [30][31][32][33] Requiring implicit bias training for interviewers can signal a commitment to equity in the recruitment process, although the efficacy of such training is unclear. 26,34 Interviewers should also be encouraged to provide transparency around DEI goals and metrics, such as percentage of residents and faculty who identify as URM and retention of URM faculty.…”
Section: Discussionmentioning
confidence: 99%